Quiz Cube: An AR mobile learning application - Protopsaltis, Aristidis; Mentzelopoulos, Markos; Ferguson, Jeffrey; Kaloyan, Kanchev (Proceedings - 11th International Workshop on Semantic and Social Media Adaptation and Personalization, SMAP 2016, 2016)
The current paper presents the Quiz Cube application and its evaluation. The Quiz Cube application is an AR mobile learning application for students and teachers to easily make and use AR UI system using fiducial marker cubes. AR as a platform is just now reaching its full potential. Since smartphones and mobile devices are now at a sufficiently large user base, it is worth looking at the potential for an extremely small form factor delivery system that is flexible, easily modified, and used by educators and students. An easily modifiable AR learning experience will present an AR Mobile platform development, interactive museums, and the chosen subject in a new style. This method can be shown to improve not only knowledge of the chosen subject through investigation, but a better understanding of development potentials for the mobile devices now ubiquitous to students. The Quiz Cube application was evaluated in three different ways and the results are presented here.
Created from Fastlane, Scopus look-up
Keywords: Augmented Reality (AR); mobile learning; Quick Response Code (QR); User Interface (UI)